Kinetic Studies of the Adsorption of Chlorinated Hydrocarbons Onto Phthalocyanine Thin Film - Misirlioglu, Banu Sungu; Ozdemir, Okan; Altindal, Ahmet (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
We have demonstrated in this paper that the chlorinated hydrocarbons can be detected by the sprayed film of the phthalocyanine (Pc) film. The effects of annealing temperature on the adsorption kinetics of chlorinated hydrocarbons onto the Pc film were also studied. Various kinetic models, such as, the pseudo first equation, second-order equation, and the Elovich equation, were selected in order to analyze the experimental data. The rate constants, equilibrium capacities, and related correlation coefficients for each kinetic model were calculated and discussed. The results showed that the sensitivity and the kinetics of the chlorinated hydrocarbons onto the Pc film strongly depend on the annealing temperature of the film. The obtained results also showed that the second-order equation was the best of the various kinetic models studied to describe the adsorption kinetic of chlorinated hydrocarbons on Pc film in a wide range of annealing temperature.
Keywords: Chlorinated hydrocarbon sensing; kinetic models; phthalocyanine; response time; sensitivity; SENSING PROPERTIES; SENSOR ARRAY; Engineering; Instruments & Instrumentation; Physics